Smart Awareness of Health Products: Synthetic Drugs, Vitamins, and Traditional Medicines at SMA Negeri 6 Medan (JURNAL PENGMAS KESTRA (JPK), 2025)
Adolescence is a critical period for the development of health-related behaviors, including decision-making regarding the use of health products. Easy access to synthetic drugs, vitamins, supplements, and traditional medicines through pharmacies and online platforms may increase the risk of irrational self-medication if not supported by adequate knowledge. Limited understanding among adolescents regarding the differences between health product categories, proper usage guidelines, and potential side effects can have negative long-term health consequences. This community service activity aimed to improve students’ health literacy concerning synthetic medicines, vitamins and supplements, and traditional medicines, while also fostering critical and responsible attitudes toward their use. The methods employed included preparatory activities, development of educational materials, coordination with the school, implementation of educational sessions, and activity evaluation. Education was delivered directly to students of SMA Negeri 6 Medan through interactive lectures, discussions, and digital-based educational games. The results demonstrated an improvement in students’ understanding of the classification, functions, labeling, and potential risks of various health products. In addition, students exhibited more selective attitudes in choosing health products and greater awareness of the importance of consulting healthcare professionals. This activity also contributed to introducing the pharmacist profession as a reliable source of drug-related information and strengthening collaboration between educational institutions and the partner school. Overall, this community service program had a positive impact on enhancing adolescent health literacy and promoting safer and more rational use of health products